Urgensi Penerapan Carbon Tax Sebagai Upaya Mitigasi Perubahan Iklim Untuk Meningkatkan Sustainable Economic Growth - Tri Winarsih; Mistri Ani; Rachmad Bayu Kurniawan; Rina Sulistyowati (Politeknik Ganesha Medan, 2025)
The increase in carbon emissions from year to year has an impact on climate change in the world, especially in Indonesia, therefore the government has stipulated Law No. 7 of 2021 concerning Harmonization of Tax Regulations (UU HPP), in Article 17 Chapter IX of the Law on HPP concerning carbon tax. The article explains that the Indonesian Government will impose a carbon tax on every carbon emission produced from both production and consumption activities. The implementation of carbon must be balanced in order to provide benefits for all parties in order to achieve economic and environmental balance. With the implementation of a carbon tax, it is hoped that it can reduce the risk of climate change that is currently occurring and can increase sustainable economic growth. This study uses a descriptive qualitative approach, with data collection techniques using interviews and documentation. While the data analysis technique uses interactive analysis with three steps including data reduction, data presentation, and drawing conclusions. The results of the study indicate that the implementation of carbon tax will be able to reduce carbon emissions that can reduce climate change, in accordance with the government's target of reducing greenhouse gas emissions by 29% with its own capabilities and 41% with international support by 2030. In addition, carbon tax also has the potential to encourage sustainable economic growth, by instilling awareness in society by creating a culture and habits for each individual, especially business actors, to transition to environmentally friendly activities, such as creating new product innovations, prioritizing the use of environmentally friendly products, and carrying out activities that minimally produce carbon gas emissions, thus leading to the realization of sustainable economic development.